Dynamic sensory description of Rioja Alavesa red wines made by different winemaking practices by using Temporal Dominance of Sensations. (23rd December 2015) - Etaio, Iñaki; Meillon, Sophie; Pérez‐Elortondo, Francisco J; Schlich, Pascal
Abstract: BACKGROUND: Although sensory description of wines in scientific literature is very large, there is an evident lack of studies describing wines from a dynamic approach. The objective of this study was to describe the evolution of the sensations perceived in red wines from Rioja Alavesa by using Temporal Dominance of Sensations (TDS) and also to compare wines made with the two winemaking procedures used in Rioja Alavesa: carbonic maceration (CM) and destemming (DS). RESULTS: Ten sensory attributes were evaluated in eight wines (four CM and four DS wines) in triplicate by a panel of 16 trained assessors. Red/black berry and woody aromas were dominant firstly, whereas heat, astringent, bitter and pungent sensations were dominant later. CM wines showed higher dominance for woody, spicy, pungent and acid sensations and lower dominance for red/black berry aroma and astringency than DS wines. CONCLUSION: This study is the first to describe Rioja wines from a dynamic approach and it also provides information about the dynamic sensory differences between wines made by CM or by DS. In this sense, this work shows the usefulness of TDS to describe and differentiate wines and to provide additional information to the conventional static descriptive analysis. © 2015 Society of Chemical Industry